2021
DOI: 10.1001/jamainternmed.2021.0839
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating HIV Screening With COVID-19 Testing in an Urban Emergency Department During the Pandemic

Abstract: The COVID-19 pandemic has had negative consequences on HIV care and prevention programs, including routine HIV screening in health care settings. 1 This has serious implications for the Ending the HIV Epidemic plan for the United States. 2 Herein, we report the results of incorporating phlebotomy for universal HIV screening into COVID-19 testing at The University of Chicago Medicine (UCM) emergency department (ED) for the purpose of maintaining screening volumes.Methods | The institutional review board at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Importantly, for HIV and hepatitis B a similar trajectory with a significant decrease in testing and linkage to care during the first months of the COVID-19 pandemic in 2020, with only testing mostly rebounding later in 2020, had also been described [ 10 , 20–25 ]. Particularly for HIV, relinkage to care of known HIV positives out of care was impacted by COVID-19, also in part due to conflicting priorities of county healthcare departments that came with the COVID-19 pandemic [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, for HIV and hepatitis B a similar trajectory with a significant decrease in testing and linkage to care during the first months of the COVID-19 pandemic in 2020, with only testing mostly rebounding later in 2020, had also been described [ 10 , 20–25 ]. Particularly for HIV, relinkage to care of known HIV positives out of care was impacted by COVID-19, also in part due to conflicting priorities of county healthcare departments that came with the COVID-19 pandemic [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that approximately 10% of ED patients had an active and/or uncontrolled infection and 4% were coinfected with at least 2 viruses, translating to approximately 750 and 30 unique viremic ED patients over the 4.5-month study period, respectively. These findings create a “call for action” for urban EDs to develop and implement systematic and integrated testing/screening strategies that improve the identification and care of patients harboring infections who come through our doors, including those with previously undiagnosed and previously diagnosed HCV, HIV, and SARS-CoV-2 (given potential long-term sequalae and/or complications of each infection) [ 36 ]. Finding appropriate methods and resources to implement these strategies will require thoughtful collaboration between engaged clinicians, hospitals, and government agencies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, individuals who seek care for COVID-19 should incorporate or even link HIV screening to COVID-19 testing as the previous report has demonstrated a considerable increase in HIV diagnoses with incorporating HIV screening into COVID-19 testing in the ED. 26 …”
Section: Discussionmentioning
confidence: 99%